Distortions to World Trade : Impacts on Agricultural Markets and Farm Incomes - Anderson, Kym (World Bank, Washington, DC, 2012)
The authors provide estimates of the impact that removing all merchandise trade distortions (including agricultural subsidies) would have on food and agricultural production, trade, and incomes. Using the latest versions of the Global Trade Analysis Project (GTAP) database and the World Bank's LINKAGE model of the global economy (projected to 2015), their results suggest farm employment, the real value of agricultural output and exports, the real returns to farm land and unskilled labor, and real net farm incomes would all rise substantially in developing country regions with a move to free merchandise trade, thereby alleviating rural poverty-despite the decline in international terms of trade for developing countries that are net food importers or are enjoying preferential access to agricultural markets of high-income countries.